Landasan Tugas dan Tanggung Jawab Pendidik dalam Meningkatkan Profesionalisme Pembelajaran - Muhammad Arif Pahsa Al Muttaqin; Fathul Janah (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
Educators are the key actors in determining the success of the educational process. However, in practice, learning is still often oriented toward the transfer of knowledge and has not fully integrated the development of students’ character, morality, and social competencies. This article aims to comprehensively analyze the foundations of educators’ duties and responsibilities and their implications for improving professional learning. This study employed a qualitative approach using a library research method by analyzing literature from national education and Islamic education perspectives. Data were analyzed through content analysis and thematic synthesis. The findings reveal that the duties and responsibilities of educators are grounded in five main dimensions: philosophical, juridical, psychological, sociological, and religious foundations. These foundations form a framework for educators’ professionalism in carrying out their roles as planners, implementers, mentors, motivators, role models, and evaluators of learning. The implementation of these foundations contributes to the creation of more humanistic, effective, and character-oriented learning. This article emphasizes that educators’ professionalism is determined not only by pedagogical competence but also by moral integrity, legal awareness, psychological understanding of students, and social and spiritual responsibility. Therefore, strengthening educators’ understanding of these foundational responsibilities is an urgent need to improve the quality of education sustainably